2020
DOI: 10.1186/s42269-020-0272-x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value and impact of wheatgrass juice (Green Blood Therapy) on increasing fertility in male albino rats

Abstract: Background and objective: The wheatgrass juice (WGJ) contains a high concentration of vitamin C. WGJ contains a lot of highly functional nutritive ingredients potent to unify the liver with the kidneys for detoxification of the organs and filtration of the blood to build a strong immune system. Also, it boosts fertility and increases sexual desire because of the high magnesium content in phytochemical pigment (chlorophyll) which boosts the production of the enzymes that restores sex steroids. Materials and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…Wheatgrass juice enhanced kidney function markers (urea, creatinine, and uric acid). It contains vitamin C and phenolic compounds, which induced liver and kidney organ detoxification and blood purification of pollutants [61].…”
Section: Discussionmentioning
confidence: 99%
“…Wheatgrass juice enhanced kidney function markers (urea, creatinine, and uric acid). It contains vitamin C and phenolic compounds, which induced liver and kidney organ detoxification and blood purification of pollutants [61].…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported high content of apigenin, quercitin, and luteolin bioactive compounds in WGJ. e presence of 70% of chlorophyll content in WGJ was also responsible for the increased antioxidant activity of the pasta [30]. Coherent results of increment of antioxidant potential were observed by the study by Devi et al [19] with the incorporation of WGJ into milk, paneer, and enrobe paneer.…”
Section: Antioxidant Activities and Bioactive Compoundsmentioning
confidence: 88%
“…Increased replacement of WGJ from 0-100% with water significantly (p < 0.05) reduced OCT from 6.10 to 5.42 minutes (Table1), while nonsignificant variation was observed at replacement levels 33 and 66%. e observed reduction in cooking time is due to an increase in acidity with the addition of ascorbic acid-rich WGJ [30]. is changes the crystalline structure of starch, and starch becomes corroded that destroys microcrystals in the starch and the glycoside bond hydrolyzed.…”
Section: Optimum Cooking Timementioning
confidence: 99%
“…Due to its various nutritious components, it can also be called "functional food" [22]. The juice form of wheatgrass is an energy beverage and has been demonstrated to upsurge fertility in male albino rats, owing to the existence of a good amount of magnesium in chlorophyll [26]. Chlorophyll is structurally composed of a tetrapyrrole ring, having a magnesium atom at the center and almost resembling the heme group in haemoglobin where the central atom is iron.…”
Section: Phytochemistry Of Wheatgrassmentioning
confidence: 99%